If
![x = {3}^{1 \4} + {3}^{ - 1 \4} x = {3}^{1 \4} + {3}^{ - 1 \4}](https://tex.z-dn.net/?f=x+%3D++%7B3%7D%5E%7B1+%5C4%7D++%2B++%7B3%7D%5E%7B+-+1+%5C4%7D+)
and
![y = {3}^{1 \4} - {3}^{ - 1 \4} y = {3}^{1 \4} - {3}^{ - 1 \4}](https://tex.z-dn.net/?f=y+%3D++%7B3%7D%5E%7B1+%5C4%7D++-++%7B3%7D%5E%7B+-+1+%5C4%7D+)
then the value of
![3({x}^{2} + {y}^{2})^{2} 3({x}^{2} + {y}^{2})^{2}](https://tex.z-dn.net/?f=+3%28%7Bx%7D%5E%7B2%7D++%2B+%7By%7D%5E%7B2%7D%29%5E%7B2%7D+)
will be?
(a) 12
(b) 18
(c) 46
(d) 64
Answers
Answered by
0
Answer:
option A is right answer
Step-by-step explanation:
I hope you me follow hii friend
Similar questions